Regional differences between North and South Greece at the turn of the century - Konstantinos Agorastos; Erotokritos Varelas; Tryfon Kostopoulos (European Regional Science Association (ERSA), 1998)
Despite the confusion surrounding the measurement of public sector outputs with respect to their demand and their distribution, the growing abundance of statistical data on public expenditures has been given incentives to the investigators of public economics to undertake research on the determinants of such expenditures. Attention has been focused upon public expenditures in an attempt to redress the imbalance emphasized on the role of taxation only. Some one hundred years ago Adolph Wagner, the German economist has suggested that as the development of a Nation proceeds government expenditure would increase. The so called "law of expanding state activity" was empirically tested by a number of investigators. Wagner's law is tested in all these studies by observing the statistical significance of the income elasticity of public expenditures. Timm was the first to interpret Wagner's law from Wagner's original writings. Since Timm's important contribution there is a Despite the confusion surrounding the measurement of public sector outputs with respect to their demand and their distribution, the growing abundance of statistical data on public expenditures has been given incentives to the investigators of public economics to undertake research on the determinants of such expenditures. Attention has been focused upon public expenditures in an attempt to redress the imbalance emphasized on the role of taxation only. Some one hundred years ago Adolph Wagner, the German economist has suggested that as the development of a Nation proceeds government expenditure would increase. The so called "law of expanding state activity" was empirically tested by a number of investigators. Wagner's law is tested in all these studies by observing the statistical significance of the income elasticity of public expenditures. Timm was the first to interpret Wagner's law from Wagner's original writings. Since Timm's important contribution there is a significant number of researchers that attempted to verify Wagner's law. In these studies it seems that the investigators have some problems in identifying the correct definitions of the dependent and independent variables that enter Wagner's relation. As we will see the problem of the correct specification of Wagner's relation is also unsolved in the present study. The present article presents an attempt to verify Wagner's law for Greece. In order to have a significant result about its validity several specifications are estimated and tested. These specifications refer to the traditional as well as to some structural ones that associate the law with some special characteristics of the Greek economy. Therefore, in order to answer the question of what the Greek households get back for their money paid on taxes, we describe and give the traditional as well as the structural specifications of Wagner's relationship that we have estimated in the present study. Especially we emphasize the role of this "Law" in the North and South regional differences of Greece, at the turn of the century. Also, we describe the statistical data we have used and comment on the econometric problems that are associated with the estimation of the relationships. Finally, we present the results of the estimations and in the concluding section we summarized our results from the point of view of their precision and the implications that Wagner's law, has when accepted, for other macroeconomic variables of the Greek economy.
Keywords: 330